Promoting the Production of Organic Products in Chiang Mai Province: the Potential Competition in ASEAN Community - สันต์สวัสดิ์, เบญจมาศ; สุทธิภาศิลป์, ปภากร (Community and Social Development Journal, 2019)
This research aims to study the potential of the agricultural communities and to propose the guideline of organic products in the communities of Chiang Mai in order to potentially compete in ASEAN Community based on the sufficiency economy philosophy. Studied on 207 agricultural communities in 25 districts of Chiang Mai province based on participatory research methodology (PAR) and analyze with SWOT Analysis (Strengths, Weaknesses, Opportunities and Threats). Discuss the results with percentage to reflect the problems and impacts that will be occur. The results showed that there are the potentially agricultural communities interested in are three groups, the fishing community of integrated local, the group of organic rice farmers and onion growers. Potential analysis found that strength is members with expertise in production, marketing, processing, and knowledge transfer. The weakness is unable to control the sales volume in each round and low bargaining power. The important opportunity is public and private sector support for regular knowledge and market support products, but obstacle is still pricing and a product volume high competitive. Therefore, it should promote the production system based on maintaining the natural balance and the use of wisdom, providing a better understanding of organic agriculture, developing organic communities, certifying the local organic products, promoting the development of organic agriculture to match the standards and requirements of the target country, and forming strong organic agriculture communities in Chiang Mai province. In order to control product quantity in each round and bargaining power.